Advancing cross-cultural perspectives on educational psychology : a festschrift for Dennis McInerney - Liem, Gregory Arief D.; Bernardo, Allan B. I.; McInerney, D. M. 1948- (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
Scholars and practitioners in the fields of education and educational psychology have come to agree that conceptions of learning and teaching, student and teacher motivation, engagement, learning and teaching strategies, and by implication, student academic achievement and teacher effectiveness are also influenced by a sociocultural context where the schooling process takes place. This raises the question if educational psychology theorizing and findings can be adopted to inform and guide teaching and learning in different cultures. As such, there is a compelling and timely need for educational psychology researchers to harness advanced cross-cultural research designs and look at the different key facets of student and teacher academic careers from a cross-cultural perspective. Dennis McInerney is one of the key pioneering figures in cross-cultural educational psychology and has also edited a book series on Research on Sociocultural Influences on Motivation and Learning (Information Age Publishing). His ideas and research have inspired many to examine the role of sociocultural context in motivation and learning. This volume is a celebration of McInerney's numerous and extensive contributions as a scholar, as well as an appreciation of his personal qualities that make him such an inspiring person. In this festschrift, the editors seek to extend the scholarly contributions of Dennis McInerney by inviting internationally recognized and leading educational psychology scholars who have inspired and been inspired by his work to re-examine their research expertise from a cross-cultural perspective. The volume aims to stimulate researchers, scholars, and graduate students in their endeavor to re-look their research from a cross-cultural lens.
Keywords: McInerney, D. M. -- (Dennis M.), -- 1948-; Educational psychology -- Cross-cultural studies.; Education -- Educational Psychology.; Educational psychology.; elektronické knihy; electronic books